Gadamer for architects - Kidder, Paul. (Abingdon, Oxon : Routledge, 2013)
"Providing a concise and accessible introduction to the work of the twentieth century's celebrated German philosopher, Hans-Georg Gadamer, this book focuses on the aspects of Gadamer's philosophy that have been the most influential among architects, educa
Includes bibliographical references (p. 126-135) and index. 1. Introduction -- 2. The play of art and the art of architecture -- 3. Historical understanding and architecture's past -- 4. Humanism in the age of science -- 5. Practical wisdom in creative co
Keywords: Gadamer, Hans-Georg, -- 1900-2002.; Gadamer, Hans-Georg, -- 1900-2002.; Architecture -- Philosophy; Mimarlık -- Felsefe